2020
DOI: 10.34172/jrhs.2020.33
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Neighborhood Crime and Hazardous Alcohol Use Among Youth in University of the Northeastern Thailand Context

Abstract: Background: The residents’ perceptions of the crime and lack of safety with their neighborhood environment, associated with stress that confers risk for drinking .While many studies have focused on adult drinking, less is known about how subjective neighborhood crime influences drinking during adolescent. We aimed to determine the association of perceived neighborhood crime and youth alcohol use. Study design: A cross-sectional study. Methods: This study was conducted on 1087 university youths from 30 neighbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Our data also showed that adolescents with high HL had significantly lower odds of consuming alcohol. This is in line with the literature where adolescents with inadequate HL in substance use were more likely to drink alcohol (Yangyuen et al, 2021). Additionally, alcohol consumption has been associated with alcohol expectancies, defined as one’s expectations for specific outcomes stemming from drinking (Goldman et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Our data also showed that adolescents with high HL had significantly lower odds of consuming alcohol. This is in line with the literature where adolescents with inadequate HL in substance use were more likely to drink alcohol (Yangyuen et al, 2021). Additionally, alcohol consumption has been associated with alcohol expectancies, defined as one’s expectations for specific outcomes stemming from drinking (Goldman et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…As these factors were contributory to obesity (aOR watch TV for more than 2 h = 1.55; 95% CI: 1.33–1.82, aOR <5 fruits and vegetables = 1.35, 95% CI: 1.17–1.55; aOR lack of physical exercise = 1.45, 95% CI: 1.15–2.12), 28 our intervention may be effective in preventing obesity. Adolescents with desired health literacy were found marginally significantly less likely to engage in risky behaviours including alcohol drinking and smoking, which were consistent with prior studies 15,29 . A study in Denmark found that inadequate health literacy was associated with poor health status, inactivity and obesity, but to a lesser extent with smoking and alcohol consumption 21 .…”
Section: Discussionsupporting
confidence: 84%
“…Parents were identified to be the health behavioural models and the key role of adolescents' health decisions. 15 They might encourage and discourage health behaviours through various means to prevent and reduce exposure to health risks. 16,17 However, the information may not always be reliable and accurate, 18 and it heavily depends on the health literacy and lifestyle habits of the parents.…”
Section: Source Of Health Informationmentioning
confidence: 99%
“…In their study, Yangyuen et al (2020) reported that perceived neighborhood crime exerted an impact on risk behaviors (e.g. alcohol use) that can possibly lead to adverse health outcomes 20 . In the current study, NH Blacks who had LBW infants were more likely to have such systemic barriers as heavy reliance on the government for assistance, residence in public housing projects, absence of transportation, and residence in unsafe neighborhoods.…”
Section: Discussionmentioning
confidence: 99%